Factors associated with refusal of preventive therapy after initial willingness to accept treatment among college students with latent tuberculosis infection in Shandong, China - Yuan, Yemin; Jin, Jin; Bi, Xiuli; Geng, Hong; Li, Shixue; Zhou, Chengchao (BMC infectious diseases, 2023)
Preventive therapy of latent tuberculosis infection (LTBI) is an important component of tuberculosis (TB) control. Research on acceptance of TB preventive therapy (TPT) is an important topic. Current studies focus on acceptability and compliance. However, it is unclear whether LTBI patients will start TPT after accepting treatment. The study assessed the factors associated with TPT refusal after initial willingness to accept treatment. Data were derived from a baseline survey of prospective study of LTBI treatment among college students in Shandong Province, China. A total of 723 students initially willing to accept TPT were included in the analysis. Stepwise logistic regression was used to explore the individual- and family-level characteristic variables that factors associated with TPT refusal after initial willingness to accept treatment. Of the 723 LTBI college students who initially had acceptance willingness, 436 (60.3%) finally refused TPT. At the individual level, non-medical students were more likely to refuse TPT [odds ratio (OR) = 4.87, 95% confidence interval (CI): 3.10-7.67)], as were students with moderate physical activity (OR = 1.45, 95% CI: 1.04-2.04). Students with boarding experience (OR = 0.49, 95% CI: 0.31-0.78) and a high level of knowledge about TB (OR = 0.97, 95% CI: 0.95-0.99) were less likely to refuse TPT. At the family level, those with high father's educational level (OR = 1.50, 95% CI: 1.07-2.10) or high household income (OR = 1.80, 95% CI: 1.20-2.71) were more likely to refuse TPT after initially accepting treatment. Factors associated with TPT refusal after initial willingness to accept treatment, such as personal (type of students, physical activity, boarding experiences, knowledge of TB) and family characteristics (father's education level, household income) among college student with LTBI, might help identify persons for whom tailored interventions could improve the start of LTBI treatment.